DIGITAL LITERACY IN GEO-SHEET-ASSISTED ANALYTIC GEOMETRY LEARNING AMONG PRE-SERVICE MATHEMATICS TEACHERS - Titin Masfingatin; Hutkemri Zulnaidi; Reza Kusuma Setyansah; Ika Krisdiana (MATEMATIKA DAN PEMBELAJARAN, 2026)
The increasing integration of technology in mathematics education highlights the importance of understanding students’ digital literacy in technology-supported learning. This study aims to describe the digital literacy profile of pre-service mathematics teachers in Geo-Sheet-assisted analytic geometry learning. Digital literacy was conceptualized into four dimensions: learning attitude, social-emotional, technical, and cognitive. A mixed-methods approach with an explanatory sequential design was employed by integrating quantitative data from a digital literacy questionnaire and qualitative data from open-ended responses, classroom observations, and interviews involving 31 pre-service mathematics teachers. The results indicate high to very high scores across the four dimensions of digital literacy. The learning attitude (M = 4.35, SD = 0.71), social-emotional (M = 4.45, SD = 0.62), and cognitive dimensions (M = 4.41, SD = 0.57) were categorized as very high, whereas the technical dimension was categorized as high (M = 3.84, SD = 0.90). Qualitative findings reveal that Geo-Sheet supports visual verification processes that help students compare representations, identify discrepancies, and refine their solutions. Students also used Geo-Sheet to interpret, evaluate, and validate mathematical representations, indicating meaningful engagement with digital tools. However, technical performance varied according to feature mastery, device limitations, and internet connectivity. The findings suggest that digital literacy in mathematics learning extends beyond technical competence and is closely associated with students’ engagement in reasoning processes involving the interpretation, comparison, and validation of mathematical representations. This study highlights the importance of designing technology-supported learning environments that foster both digital literacy and mathematical reasoning in teacher education.   Keywords: Analytic Geometry; Digital Literacy; Geo-Sheet; Pre-Service Mathematics Teachers; Geogebra-Based Learning